1997
DOI: 10.1097/00010694-199707000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter of Suggested Spodic Horizons in Relic Ornithogenic Soils of Coastal Continental Antarctica (Casey Station, Wilkes Land) in Comparison With That of Spodic Soil Horizons in Germany

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…White et al (2007) used pyrolysis GC-MS to examine 19 soils collected from a variety of circumpolar regions and found that these soils were carbohydrate rich. Solid-state 13 C NMR characterization studies of soil OM from the Arctic, Antarctic, and northern alpine regions have collectively reported that alkyl and O-alkyl structures dominated the NMR spectra (Beyer et al, 1995(Beyer et al, , 1997(Beyer et al, , 2001Dai et al, 2001Dai et al, , 2002Sjögersten et al, 2003;Pautler et al, 2010;Pedersen et al, 2011). These studies provide the underlying basis for concern since labile OM constituents (i.e., O-alkyl components) are particularly susceptible to climate change.…”
Section: Soil Organic Matter Structural Shifts With Soil Warmingmentioning
confidence: 99%
“…White et al (2007) used pyrolysis GC-MS to examine 19 soils collected from a variety of circumpolar regions and found that these soils were carbohydrate rich. Solid-state 13 C NMR characterization studies of soil OM from the Arctic, Antarctic, and northern alpine regions have collectively reported that alkyl and O-alkyl structures dominated the NMR spectra (Beyer et al, 1995(Beyer et al, , 1997(Beyer et al, , 2001Dai et al, 2001Dai et al, , 2002Sjögersten et al, 2003;Pautler et al, 2010;Pedersen et al, 2011). These studies provide the underlying basis for concern since labile OM constituents (i.e., O-alkyl components) are particularly susceptible to climate change.…”
Section: Soil Organic Matter Structural Shifts With Soil Warmingmentioning
confidence: 99%
“…The chemical shifts are given relative to nitromethane (=0 ppm). Peak assignments were taken from earlier references (Clinton et al 1995;Knicker et al 1996;Beyer et al 1997;Mahieu et al 2000). Actual spectral boundaries used for peak area determination were the natural 'valleys' closest to the indicated chemical shift values.…”
Section: Cross-polarization Magic Angle Spinning (Cp/mas) 15 N-nmrmentioning
confidence: 99%
“…Spodosols are the unique order of soils that present clear evidence of elluviation and illuviation of organic matter (OM) throughout the profile (Soil Survey Staff, 1999). These soils occur worldwide from boreal to tropical climates (Ugolini et al, 1987;Blume et al, 1996;Beyer et al, 1997;Stützer, 1999;Lundström et al, 2000a,b). In cold climates podzols occur as zonal soils and can develop on many different types of rocks, whereas in tropical regions intrazonal podzols occur in lowlands on poor parent material such as quartz-rich sandy coastal plain sediments or on quartzitic rocks at various altitudes.…”
Section: Introductionmentioning
confidence: 99%